Familial reciprocal translocation t(8;17)(p23;q21) in a woman with recurrent spontaneous abortion - Al-Ashi, Shadi F.; Sharif, Fadel A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
This work presents the results of cytogenetic analysis of a couple referred to our genetics laboratory with ten first trimester abortions and one IVF failure. The male showed a normal (46, XY) karyotype whereas the female was found to carry an apparently balanced reciprocal translocation [46, XX, t(8;17)(p23;q21)]. Two sisters and two brothers of the eight siblings of the female proved to have the same translocation. Although the female’s father is deceased and his sample was not available for investigation. The origin of this translocation must be paternal since the female’s mother harbored a normal karyotype. It is concluded that the history of recurrent pregnancy losses in the couple is due to the production of unbalanced gametes in the female as a result of the reciprocal translocation she has and the couple was advised to undergo a PGD for embryo selection prior to their future IVF trials. The authors also recommend that all RSA couples with normal routine work-up results should be offered chromosomal analysis without delay.